Antecedents, process, and equity outcomes: A study about collaborative governance - Dany Flávio Tonelli; Lindsay Sant'Anna; Elenice Barcelar Abbud; Suelen Aparecida de Souza (Cogent Business & Management, 2018)
The purpose of the present study is to draw a general structure, based on a scoping literature review, to better understand the collaborative governance, as well as their elements and complexity. After defining the search meshes and selecting the criteria to apply, 35 papers about were found in the Web of Knowledge® database. The analysis identified its central elements and features, in terms of Antecedents, Collaboration Process, and Equity Outcomes, each of them with its properties. The study highlights the properties of each category, and it provides the possibility to improve the quality of the decision-making processes in collaborative arrangements.
Keywords: 650